(untitled) - Sawada, Toshizo (Tokyo, 1977)
Tyical fish of 457 species in Indonesia - mainly marine species are picked up. These species are classified into 17 groups for convinience sake.
Keywords: Cá,Fishes; Indonesia,Indonesia